2016
DOI: 10.1097/wnr.0000000000000674
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of riboflavin transporter 2 contributes toward progression and invasion of glioma

Abstract: Human riboflavin transporter 2 (RFT2) encoded by the SLC52A3 gene is a member of the SLC52 family that has been shown to play a key role in riboflavin homeostasis. Recently, a number of studies have shown that RFT2 is important in the development of several cancers, including esophageal squamous cell carcinoma, gastric cancer, and cervical cancer. However, its expression and function in glioma have not yet been explored. In this study, we found that RFT2 was overexpressed in glioma samples compared with normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Increased expression of the solute carrier family of riboflavin transporters ( SLC52A3, PEP = 3.6e–2) is intriguing, considering riboflavin is a precursor to the complex II substrate flavin adenine dinucleotide. Findings of mutations and deficiency of the brain-specific transporter SLC52A3 are linked to motor neuron diseases (Brown-Vialetto-Van Laere syndrome and Fazio-Londe disease) ( Bosch et al, 2011 ; Manole et al, 2017 ), while its overexpression was shown to enhance the proliferatory capability of human glioma, mediating its effect through suppression of proapoptotic proteins and upregulation of matrix metalloproteinases (MMPs), specifically MMP-2 and MMP-9, which have been shown to correlate with both CSF Aβ and tau levels from AD patients ( Fu et al, 2016 ; Wang et al, 2014 ). Understanding the signaling pathways of SLC52A3 warrants further research for validity as clinical diagnostic markers and for dietary considerations ( Jones et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Increased expression of the solute carrier family of riboflavin transporters ( SLC52A3, PEP = 3.6e–2) is intriguing, considering riboflavin is a precursor to the complex II substrate flavin adenine dinucleotide. Findings of mutations and deficiency of the brain-specific transporter SLC52A3 are linked to motor neuron diseases (Brown-Vialetto-Van Laere syndrome and Fazio-Londe disease) ( Bosch et al, 2011 ; Manole et al, 2017 ), while its overexpression was shown to enhance the proliferatory capability of human glioma, mediating its effect through suppression of proapoptotic proteins and upregulation of matrix metalloproteinases (MMPs), specifically MMP-2 and MMP-9, which have been shown to correlate with both CSF Aβ and tau levels from AD patients ( Fu et al, 2016 ; Wang et al, 2014 ). Understanding the signaling pathways of SLC52A3 warrants further research for validity as clinical diagnostic markers and for dietary considerations ( Jones et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…As for the cancer risk, riboflavin supplement was thought to reduce various types of cancer risks, 13 and several cancer risk research found that SLC52A3 SNPs was associated with oesophageal cancer risk, 14‐16 probably activated by NF‐κB p65/Rel‐B 17 . Previous studies also found that SLC52A3 rs13042395 C > T change could promote glioma cancer cell progression and migration in vivo and in vitro 18 . Interestingly, researchers found that SLC52A3 rs13042395 TT genotype favoured reduced lymph node metastasis rate and longer relapse‐free survival in oesophageal squamous cell carcinoma 19 .…”
Section: Discussionmentioning
confidence: 99%
“…RFVT3, in particular, was shown to be 187-fold more expressed in SCC compared to healthy tissue [50]. High amounts of RFVT3 were also found in esophageal squamous cell carcinoma, squamous cell carcinoma, and glioma [51][52][53]. Moreover, the SLC42A3 protein level was seen to increase with the stepwise development of esophageal squamous cell carcinoma [54].…”
Section: Riboflavin Transportersmentioning
confidence: 92%